Pheochromocytomas, Paragangliomas and Disorders of the Sympathoadrenal System Clinical Features, Diagnosis and Management (Contemporary Endocrinology,, 2018)
Providing a comprehensive review of the most up-to-date evidence, this book presents the latest biology, diagnosis and management for pheochromocytomas, paragangliomas and related disorders of the sympathoadrenal system. Many new areas, including genetic syndromes, have evolved, and these are insufficiently appreciated among practitioners. A discussion of the basics of catecholamine biology sets the stage for presentations of the pathology, clinical features, and diagnosis of these tumors, including localization and imaging. Medical, anesthetic and surgical management of pheochromocytomas and paragangliomas follow, including case material. Additional chapters discuss pheochromocytoma in pediatrics and in pregnancy, both pure and hypoglycemia-associated autonomic failure, and the role of the sympathetic nervous system in hypertension. These diseases are relatively rare, but many, if not most, go undiagnosed during life: If promptly diagnosed and appropriately treated, they are usually completely curable; if undiagnosed or mistreated, they are typically terminal. Bringing the most current knowledge to bear, Pheochromocytomas, Paragangliomas and Disorders of the Sympathoadrenal System will be a valuable resource for practicing endocrinologists, endocrine surgeons, internists and endocrine fellows faced with diagnosing and managing these conditions.